Clinical Findings Documenting Cellular and Molecular Abnormalities of Glia in Depressive Disorders - Czéh, Boldizsár; Nagy, Szilvia A. (Frontiers in Molecular Neuroscience, 2018)
Depressive disorders are complex, multifactorial mental disorders with unknown neurobiology. Numerous theories aim to explain the pathophysiology. According to the “gliocentric theory”, glial abnormalities are responsible for the development of the disease. The aim of this review is to summarize the rapidly growing number of cellular and molecular evidences indicating disturbed glial functioning in depressive disorders. We focus here exclusively on the clinical studies and present the in vivo neuroimaging findings together with the postmortem molecular and histopathological data. Postmortem studies demonstrate glial cell loss while the in vivo imaging data reveal disturbed glial functioning and altered white matter microstructure. Molecular studies report on altered gene expression of glial specific genes. In sum, the clinical findings provide ample evidences on glial pathology and demonstrate that all major glial cell types are affected. However, we still lack convincing theories explaining how the glial abnormalities develop and how exactly contribute to the emotional and cognitive disturbances. Abnormal astrocytic functioning may lead to disturbed metabolism affecting ion homeostasis and glutamate clearance, which in turn, affect synaptic communication. Abnormal oligodendrocyte functioning may disrupt the connectivity of neuronal networks, while microglial activation indicates neuroinflammatory processes. These cellular changes may relate to each other or they may indicate different endophenotypes. A theory has been put forward that the stress-induced inflammation – mediated by microglial activation – triggers a cascade of events leading to damaged astrocytes and oligodendroglia and consequently to their dysfunctions. The clinical data support the “gliocentric” theory, but future research should clarify whether these glial changes are truly the cause or simply the consequences of this devastating disorder.